Clinical features of incontinentia pigmenti with emphasis on dermatoglyphic findings - (:unkn) unknown (Journal of Clinical Pediatric Dentistry, 2001)
Incontinentia pigmenti is a syndrome characterized by both systemic and oral manifestations. Presented here are the dental, clinical, radiological, genetic and dermatoglyphic findings of a 6 year old female case and her family members. The following features were apparent: oligodontia in maxillary and mandibular arches in both dentition, peg-shaped incisors and brown lessions on the body surface. No other problems were observed. The case had remarkable dermatoglyphic findings such as hypothenar loops associated with distally displaced axial triradii on both palms, reduced total finger and summed palmar a-b ridge-counts, decreasing plantar pattern intensity on the left sole. The other family members had similar dermatoglyphic characteristics. The paternal grand father, the father and the brother had eye defects.